School Counselors Strategies in Promoting Psychological Well-Being and Addressing Bullying Related Trauma - Eko Perianto; Anis Anggraini; Cinta Marsela Valensia Iban Saputri; Eko Perianto; Anis Anggraini; Cinta Marsela Valensia Iban Saputri (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study aims to describe how school counselors help students achieve psychological well-being and how to overcome trauma caused by bullying at school. This study uses a qualitative descriptive method, with data collection techniques including interviews, observation, and documentation. The subjects or informants in this study were school counselors, students, students who were bullies, and students who were victims of bullying. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. Data validity used triangulation of sources, techniques, and time. The results of the study indicate that student psychological well-being at school is achieved through several activities carried out by school counselors. Services include individual counseling, group counseling, classical guidance, thematic counseling programs, career guidance, and crisis intervention. School counselors also play a strategic role in fostering student psychological well-being through structured, responsive, and collaborative services. School counselors address the impact of trauma caused by bullying at school through several strategies, including prevention and mitigation. Prevention strategies include counseling services on the dangers of bullying, education on communication ethics, wise use of social media, and routine patrols in the school environment. Mitigation strategies include individual counseling for both perpetrators and victims to prevent trauma and mediation to resolve conflicts. Both prevention and intervention strategies are effective in restoring victims' emotional well-being, increasing motivation to learn, and raising awareness among perpetrators to prevent repeat bullying.